Pemetaan Pengetahuan Guru Tentang Pelaksanaan K13 di SDN Gugus Wilayah II Kecamatan Kuala Kabupaten Langkat - Rizki Rahayu; Mustika Adriana; Usiono Usiono (Yayasan Rahmat Islamiyah, 2021)
This study aims to obtain an overview of the knowledge mapping of teachers at SDN Gugus Region II, Kuala Subdistrict, Langkat Regency from the aspect of knowledge about the characteristics of K13, the principles of developing K13, the structure of K13 in Elementary Schools, Implementation of K13 and the Principles of developing lesson plans. This type of research is descriptive research. Data collection techniques in this study were interviews and questionnaires. This research was conducted at SDN Cluster Region II, Kuala District, Langkat Regency. The subjects of this study were teachers of grades I, II, IV and V who had implemented the 2013 curriculum. The population in this study was SDN Gugus Region II, Kuala District, Langkat Regency. The sample in this study were 20 teachers at SDN Cluster Region II, Kuala District, Langkat Regency.The results of this study indicate that the knowledge of teachers at SDN Cluster Region II is quite good. This can be seen from the answers given by the teacher on the questionnaire sheet. It's just that there are some teachers who don't know about K13 knowledge well, due to the lack of training and mentoring at SDN Gugus Region II, Kuala District, Langkat Regency. Thus, it can be concluded that the teacher's knowledge of the 2013 curriculum is quite good. Keywords: Teacher Knowledge, 2013 Curriculum, Elementary School